Toleransi Beragama dalam Al-Quran Menurut Pandangan Mufasir Nusantara: Studi Komparasi Pandangan Shaikh Nawawi Al-Bantani, Muhammad Hasbi Al- Shiddieqy dan Buya Hamka - Ach Readi; Ghozi Mubarok (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
Diversity is an inherent aspect of social life, particularly in a multicultural society like Indonesia, which comprises various ethnicities, races, cultures, and religions. Differences in belief should not lead to conflict but instead foster mutual respect and peaceful coexistence. Islam, as a religion of rahmatan lil ‘alamin (a blessing for all creation), upholds tolerance as a fundamental social value. However, the Qur'an outlines certain limits to ensure tolerance does not compromise core principles of faith. This study aims to explore the concept and boundaries of religious tolerance from the perspectives of three prominent Nusantara exegetes: Shaikh Nawawi al-Bantani, Muhammad Hasbi al-Shiddieqy, and Buya Hamka, while identifying similarities and differences in their views. Using a library research method with a comparative descriptive analysis, the study examines their interpretations. The findings reveal that all three scholars share a consistent understanding of tolerance as an attitude of mutual respect, understanding, and acceptance of differences to achieve a peaceful and harmonious society. Nevertheless, they differ in defining its limits. Nawawi al-Bantani includes aspects of faith and politics, Hasbi emphasizes moral-based social interactions, and Hamka confines tolerance to social relations not related to faith.